Small Group Discussion Toward Students’ Reading Comprehension: Effective - Rusmiati, Rusmiati; Fitriani, Fitriani; Zakaria, Rahmanita (Ta'dib: Jurnal Pemikiran Pendidikan, 2021)
The purpose of this study was to find out whether or not small group discussion was effective in increasing students’ reading comprehension. Quantitative method was applied in this research by using quasi experimental design with two independent samples. The population taken in this research was the eighth grade students of SMP N 2 Takengon which was 221 students in total, while the samples were class VIII-2 and VIII-3 which were opted by applying random sampling. To collect the data, test was carried out to see the influence of applying SGD in the experimental class. From the data analysis, it can be seen that the mean score for experimental class before and after treatment were 46 and 66,5, while the mean score for control class were 45 and 53. The result of t-test showed that t-score (5,25) is higher than t-table (1,9) indicating that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. It signifies that small group discussion was effective in increasing students’ reading comprehension. It is suggested that the teachers apply this technique in teaching and learning.